Problematika Pembelajaran penjas Secara Daring SMK Se-Kabupaten Karawang Dimasa Pandemi Covid-19 - Bagus Ade Marla; Febi Kurniawan; Saepul Ma’mun (Peneliti.net, 2022)
This study aims to find out the problems of courageous physical education learning at SMK in Karawang Regency during the covid-19 pandemic. Results Based on the research, it is shown that the problems that arise in the physical education learning process with the bold method during the COVID-19 pandemic in State Elementary Schools throughout the Jetis District of Bantul are in the high category. This pandemic causes learning to be carried out boldly to prevent transmission. Brave learning is one of the online learning methods or carried out via the internet. Learning developed to expand educational services and also increase the availability of educational services. Although it is not the same as face-to-face learning in class, learning that dares to provide solutions to avoid the transmission of the current epidemic is happening. The hope related to online learning is the first hope, after conditions return to normal or the Covid-19 outbreak has ended, the hope of teachers in addition to learning in the classroom, online learning can still be carried out to train the skills of teachers and students in the era of the 4.0 century. The hope of these two learnings is as an alternative for teachers in applying learning models. It aims to increase knowledge and apply the use of technological advances properly and correctly. The third hope is that there is special treatment for students who have difficulty in learning. Fourth hope, this online learning model is good to use but needs to be added with an offline learning model. This is because if it is only online learning, the honesty and independence of students in doing assignments is less controlled. So it would be good if this online learning model was continued by adding face-to-face learning